FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA ROOM ATTENDANT DI HOTEL GRAND CENTRAL PEKANBARU - Sugianti "; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Performance of one employee with another in one company is very different depending on the factors that influence it. The feeling of satisfaction that they get while doing their work could make them to work optimally and show their best result. The purpose of this study is to find out the description of work environment and the factors that influence performance of Room Attendant at Grand Central Hotel of Pekanbaru. The work environment of Room Attendant at Grand Central Hotel of Pekanbaru is supported by 3 facilities, which are facility of work completeness, facility of social and facility of equipment to complete Room Attendant requirements. Based on the result obtained from the result of the spread questionnaires to the respondents as many as 9 people that are Room Attendant employees of Grand Central Hotel of Pekanbaru, the data processing showed that there are 3 factors that influence the performance of Room Attendant at Grand Central Hotel of Pekanbaru and from 9 respondents, 53% stated that they were strongly agree on the individual factor, 72% agreed on the work environment factor, and 60% stated that they were strongly agree on the family environment factor that influence the performance of Room Attendant at Grand Central Hotel of Pekanbaru.Keywords: performance, housekeeping, room attendant